Dual-Band FSS Backed Printed Antenna with Fractal Geometry for Wearable Applications - Anand Krishnan M.J.; Samantaray D.; Mohamed A.; Saha C.; Bhattacharyya S. (My University, 2025)
In this paper, a dual-band fractal-based printed wearable antenna backed with frequency selective surface (FSS) array is proposed for C- and X-band applications. The proposed antenna is designed to operate at 6 and 8 GHz with a high realized gain of 8.5 dBi and 9.4 dBi, respectively. The realized antenna provides a narrow band impedance bandwidth of 70 MHz centered at 6.01 GHz in the first band and UWB bandwidth of 780 MHz centered at 8.05 GHz for the second band, with maximum realized gain of 8.5 dBi and 9.4 dBi, respectively. The ground, FSS unit cell, reflector sheet and the radiating patch of antenna have been made using copper while styrofoam is used as the substrate material. The proposed design can be embedded on fabrics and is a potent candidate for wearable applications. © 2021, Springer Nature Singapore Pte Ltd.